Cardiac disease in neonates. Issue 1 (January 2023) - Ali, Mahmoud; Arnold, Philip
Abstract: Congenital heart disease occurs in approximately 8 in every 1000 births, making it the most common significant congenital abnormality. There is a wide range of lesions and the impact of these during neonatal life will be extremely variable: some will require major cardiac surgery in the first weeks of life, whilst other lesions will have little impact on the child's health. Cardiac disease also has implications for management, and outcome, of neonates undergoing non-cardiac surgery.